2022
DOI: 10.3390/ijms231710174
|View full text |Cite
|
Sign up to set email alerts
|

Distress-Mediated Remodeling of Cardiac Connexin-43 in a Novel Cell Model for Arrhythmogenic Heart Diseases

Abstract: Gap junctions and their expression pattern are essential to robust function of intercellular communication and electrical propagation in cardiomyocytes. In healthy myocytes, the main cardiac gap junction protein connexin-43 (Cx43) is located at the intercalated disc providing a clear direction of signal spreading across the cardiac tissue. Dislocation of Cx43 to lateral membranes has been detected in numerous cardiac diseases leading to slowed conduction and high propensity for the development of arrhythmias. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 65 publications
0
9
0
Order By: Relevance
“…9,21 A previous study showed that the expression of miR-1 increased and was subsequently regulated to lower the expression of Cx43 under oxidative stress. 20 Our investigation demonstrated that while CFs-exo boosted the expression of Cx43 in ventricular tissues, however, Sev-CFs-Exo significantly enhanced it. Meanwhile, both of them could reduce the distribution of Cx43 to the lateral membrane.…”
Section: Discussionmentioning
confidence: 57%
See 1 more Smart Citation
“…9,21 A previous study showed that the expression of miR-1 increased and was subsequently regulated to lower the expression of Cx43 under oxidative stress. 20 Our investigation demonstrated that while CFs-exo boosted the expression of Cx43 in ventricular tissues, however, Sev-CFs-Exo significantly enhanced it. Meanwhile, both of them could reduce the distribution of Cx43 to the lateral membrane.…”
Section: Discussionmentioning
confidence: 57%
“…19 The principal connexin in the ventricle is connexin 43 (Cx43), and its expression is regulated by microRNA-1. 20 Abnormal expression and location of Cx43 in ischemia-reperfusion myocardium is closely related to RA, and up-regulation of Cx43 expression can reduce the risk of RA. 21 Sevoflurane is one of the most commonly utilized halogenated inhalational anesthetics in CPB surgery because of its low blood-gas partition coefficient, high anesthetic efficiency and no discernible influence on heart rates (HR).…”
Section: Introductionmentioning
confidence: 99%
“…Meraviglia V et al [ 69 ] reported that ELSM significantly reduced the expression of connexin43 (Cx43) by increasing the acetylation of Cx43 on HL-1 cardiomyocytes at 0.5 Hz for 24 h, suggesting that ELSM may reduce the expression of Cx43 by affecting the protein level of Cx43 and reducing cardiomyocyte-to-cardiomyocyte communication. Another report suggested that Cx43 expression was highly sensitive to ELSM in a frequency-dependent manner that high stimulation frequency leads to a substantial reduction in global Cx43 expression in murine-induced pluripotent stem cell-derived cardiomyocytes by promoting the expression of microRNA-1, which targets Cx43 [ 70 ]. It would be interesting to see whether ELSM inhibits Cx43-dependent cell-cell communications and enhances EV-mediated intracellular communications.…”
Section: Limitations and Future Directionmentioning
confidence: 99%
“…Cx43 is found in gap junctions and is critical for both metabolic and electrical coupling of cardiomyocytes as well as other cells [ 52 ]. In fact, a loss of function in the gap junctions has been associated with HFrEF as well as lethal arrhythmias [ 18 , 53 ]. BAG3 has also been shown to regulate the physiologic maintenance and pathologic degradation of Cx43.…”
Section: Cellular Function Of Bag3mentioning
confidence: 99%